Measures of sustainable construction projects performance - Oke, Ayodeji Emmanuel (Emerald Publishing, 2022)
"Oke builds on years of knowledge and research providing a comprehensive discussion on various metrics and variables for measuring the success and performance of sustainable construction projects; culminating in an essential text for various stakeholders concerned with the management and administration of construction and infrastructure projects in the Architecture, Engineering, Construction and Operation (AECO) industry." -- Back cover
Keywords: Projektmanagement; Bauwesen; Nachhaltigkeit; Sustainable construction